2023
DOI: 10.3390/life13020561
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Gut Microbiota and Its Metabolite Short-Chain Fatty Acids in Neonatal Necrotizing Enterocolitis

Abstract: Short chain fatty acids (SCFAs), the principle end-products produced by the anaerobic gut microbial fermentation of complex carbohydrates (CHO) in the colon perform beneficial roles in metabolic health. Butyrate, acetate and propionate are the main SCFA metabolites, which maintain gut homeostasis and host immune responses, enhance gut barrier integrity and reduce gut inflammation via a range of epigenetic modifications in DNA/histone methylation underlying these effects. The infant gut microbiota composition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 147 publications
0
6
0
Order By: Relevance
“…In term infants born to GDM women, GM, such as Bifidobacterium, is related to the decrease of SCFAs content in feces ( Soderborg et al., 2020 ). Bifidobacterium can utilize human milk oligosaccharides (HMOs) through related degradation enzymes, thereby increasing the production of butyrate, propionate and other SCFAs ( Gopalsamy et al., 2019 ; Alsharairi, 2023 ). The results of a control trial showed that butyrate could reduce intestinal inflammation in mice, and the expression of M2 macrophage related protein Arg1 was significantly increased.…”
Section: Mechanism Of Action Of Scfas In Pementioning
confidence: 99%
“…In term infants born to GDM women, GM, such as Bifidobacterium, is related to the decrease of SCFAs content in feces ( Soderborg et al., 2020 ). Bifidobacterium can utilize human milk oligosaccharides (HMOs) through related degradation enzymes, thereby increasing the production of butyrate, propionate and other SCFAs ( Gopalsamy et al., 2019 ; Alsharairi, 2023 ). The results of a control trial showed that butyrate could reduce intestinal inflammation in mice, and the expression of M2 macrophage related protein Arg1 was significantly increased.…”
Section: Mechanism Of Action Of Scfas In Pementioning
confidence: 99%
“…In agreement with the typical gut microbiota developmental pattern, key species within the Lachnospiraceae and Ruminococcaceae families produce butyrate, while Bacteroides species are common propionate producers [161]. These species possess a comprehensive array of enzymes for breaking down dietary fibers into these SCFAs [162]. Moreover, certain species more abundant in older infants, such as Bacteroides and Clostridium, might employ a range of amino acids derived from dietary proteins to produce BCFAs [163].…”
Section: Diversity Of Solid Food Introductionmentioning
confidence: 65%
“…The change in DNA methylation induced by SCFAs is an important epigenetic modification [ 67 ]. During the occurrence and development of NAFLD, the hypo-and hypermethylation genes such as growth factor-α ( PDGFα ), phospholipase C gamma 1 ( PLCG1 ), caspase 1 ( CASP1 ) are epigenetic regulated and exacerbate the progression of NAFLD by participating in immune response, oxidative stress, and liver lipid degeneration [ 68 ].…”
Section: Epigenetic Mechanisms Of Scfas In Improving Nafldmentioning
confidence: 99%